Bitcoin return dynamics volatility and time series forecasting - Anand, Punit; Sharan, Anand Mohan (International Journal of Financial Studies, 2025)
Bitcoin and other cryptocurrency returns show higher volatility than equity, bond, and other asset classes. Increasingly, researchers rely on machine learning techniques to forecast returns, where different machine learning algorithms reduce the forecasting errors in a high-volatility regime. We show that conventional time series modeling using ARMA and ARMA GARCH run on a rolling basis produces better or comparable forecasting errors than those that machine learning techniques produce. The key to achieving a good forecast is to fit the correct AR and MA orders for each window. When we optimize the correct AR and MA orders for each window using ARMA, we achieve an MAE of 0.024 and an RMSE of 0.037. The RMSE is approximately 11.27% better, and the MAE is 10.7% better compared to those in the literature and is similar to or better than those of the machine learning techniques. The ARMA-GARCH model also has an MAE and an RMSE which are similar to those of ARMA.
Keywords: ARMA; ARMA-GARCH; Econometrics; Economics; Financial economics; MAE; Mathematics; RMSE; Series (stratigraphy); Statistics; Time series; Volatility (finance); bitcoin; dept.fin; time series

US bank lending to small businesses: an analysis of covid-19 and the paycheck protection program - Abugri, Benjamin A.; Osah, Theophilus T. (Journal of Risk and Financial Management, 2025)
This paper examines the characteristics of banks and their lending behavior in relation to Paycheck Protection Program (PPP) loans and commercial and industrial (C&I) loans to small businesses during the COVID-19 pandemic. Our findings show that lenders facing greater risk tended to lend more PPP loans, consistent with the risk-aversion theory. Specifically, banks with a higher loan–deposit ratio, lower overall profitability, poorer loan quality, and higher exposure to risks in business (C&I) loans are characterized by higher PPP loans. C&I loans to all businesses are negatively related to the loan–deposit ratio and loan loss allowance ratio, but are positively linked with the capital ratio. However, we find important differences in C&I lending to small businesses versus large businesses. Furthermore, there is evidence regarding the success of targeting PPP loans towards more productive sectors of the US economy. Using FDIC-defined banks’ lending specializations, we show that banks focused on international lending had a limited role in PPP lending.
Keywords: 2019-20 coronavirus outbreak; Business; COVID-19 pandemic; Coronavirus disease 2019 (COVID-19); Medicine; Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2); US banks; Virology; commercial and industrial loans; dept.fin; paycheck protection program; peer-reviewed; risk aversion; small business lending

Productivity Gaps and Global Systematic Risk Exposure: Pricing Country-Industry Portfolios - Anand, Punit; Balvers, Ronald J. (2020)
Shocks transmitted from productivity leaders to lagging economies are systematic sources of risk. Global technology and knowledge diffusion leads to predictable patterns in productivity dynamics across countries and industries. Technology gaps determine the level of exposure to the systematic productivity shocks. Firms in a country-industry with larger technology gaps relative to the world leader are more dependent on the leader’s innovations compared to their own productivity improvements. They thus have higher loadings on the leader productivity shocks and higher average stock returns. For OECD panel data, a country-industry’s technology gap significantly predicts the stock returns of the country-industry: holding the quintile of country-industry portfolios with the largest gaps and shorting the quintile with the smallest gaps generates annual returns of 9.8% (6.7% after risk adjustment with standard factors). A factor representing the technological productivity gap explains country-industry portfolio returns substantially better than standard factor models. Loadings on leader-country productivity shocks have substantial correlation with technology gaps, and leader productivity shocks are more important for stock returns than idiosyncratic productivity shocks. These findings support that the technology gaps and associated higher average returns are indeed linked to systematic risk.
Keywords: International Equity Returns; OECD Countries; Production-Based Asset Pricing; Productivity Gap; Technology Diffusion; Total Factor Productivity; dept.fin

Ex Ante Predictability of Stock Returns in a Frontier Market - Nguyen, Khoa (Applied Finance Letters, 2022)
This study reports results on the ex ante predictability of stock returns using real-time stock market data in Vietnam, a frontier market, from June 2008 to June 2021. Countries classified as a frontier market are often known for currency manipulation, financial market illiquidity, and political instability. Despite the enormous risk usually posed by these inefficiencies, potential profits are large and achievable for many investors. This study provides evidence on existing a strategy to form out-of-sample long portfolios that generate statistically significant and positive mean monthly returns even in the presence of transaction costs. I also justify the magnitude of these returns by showing that they exceed those of VnIndex and MSCI Vietnam Index. The results reject the hypothesis that the stock prices in Vietnamese market follow random walks, thus oppose the stock market efficiency hypothesis. Evidence found in this study provides a better understanding of informational efficiency in a frontier equity market setting. Specifically, there are several implications on portfolio selection strategies, stock price patterns, and trading behavior bias related to Vietnamese stock market can be drawn from this study.
Keywords: dept.fin; peer-reviewed

External vs. In-House Advising Service: Evidence from the Financial Industry Acquisitions - Huang, Jian; Yu, Han; Zhang, Zhen (Journal of Risk and Financial Management, 2023)
This study analyzes the wealth impact on M&A deals when the acquirers in the financial industry utilize external versus in-house advising services. A quasi-natural observatory setting is applied to investigate the costs and benefits of retaining a financial advisor. Based on agency theory, information asymmetry and conflict of interest both exist in the setting of M&A deals when acquirers use advisory services. We first find that almost 40% of financial acquirers are more likely to use in-house advising services, the frequency of which is significantly higher than that of non-financial acquisitions previously documented. Further, we find that in certain complex deals of greater information asymmetry, the frequency of retaining advisory services in-house is even higher. This finding suggests that for financial acquirers who possess expertise in the M&A market, the concern of conflict of interests (i.e., misaligned incentives) between the acquirers and their advisors are more salient than the concern of information asymmetry. More importantly, using the two-stage regressions method controlling the endogeneity of the choice between in-house versus external advisory services, this study finds that the three-day abnormal returns around the acquisition announcements are 4.5% higher for the acquirers retaining in-house advisory services, 18.7% higher for the corresponding target, and the combined merger gains are 2.2% higher. Overall, our findings provide direct evidence of the agency cost when an external advisor is hired and document the incremental values that the financial acquirers’ in-house advisory services may create.
Keywords: agency costs; dept.fin; external advisors; financial industry; in-house advisors; information asymmetry; peer-reviewed

Ex-ante performance of REIT portfolios - Birz, Gene; Devos, Erik; Dutta, Sandip; Nguyen, Khoa; Tsang, Desmond (Review of Quantitative Finance and Accounting, 2022)
The Real Estate Investment Trust (REIT) market has become an increasingly important vehicle for alternative investment for equity investors. While existing research examining the cross-section of REIT returns usually employs standard risk factors in the in-sample models, it can only show the ex-post performance of REIT portfolios. The goal of our paper is to examine the ex-ante performance of REIT portfolios (i.e., the ability of investors to earn abnormal returns in real time). We employ the out-of-sample methodology of Cooper, Gutierrez, and Marcum (2005), and show that ex-ante performance of REIT portfolios is rather weak. For about half of our 19-year sample over the period of 1999 to 2017, the portfolio performances of REITs chosen ex-ante do not beat the performances of the FTSE-NAREIT or the CRSP Equal-Weighted index. After adjusting for transaction costs, the REIT portfolios significantly further underperform their benchmarks. Overall, our findings suggest that the market is relatively efficient in the REIT sector, and it is difficult for investors to devise trading strategies that improve the ex-ante performance of REIT portfolios, based on standard risk factors.
Keywords: Abnormal returns; Out-of-Sample; Portfolio management; Predictability; REITs; Real estate; dept.fin; peer-reviewed

Measuring systematic risk from managerial organization capital - Yildirim, Alev; Allen, Linda (Journal of Business Finance & Accounting, 2021)
Keywords: dept.fin; peer-reviewed

A coronavirus outbreak and sector stock returns: a tale from the first ten weeks of 2020 - Nguyen, Khoa Huu (Applied Economics Letters, 2021)
This paper examines early impacts of the COVID-19 outbreak on stock returns of 11 sectors using the firm-level stock price data from 10 countries. Results show that investors across sectors and countries respond differently during the outbreak. Communication Services, Consumer Staples, Health Care, Information Technology, and Utilities sectors consistently perform relatively well, compared to other sectors, in all countries except Italy, Japan and U.S. Conversely, Energy sector suffers greatest abnormal negative returns, among all sectors, in countries including Canada, Italy, U.K. and U.S. Furthermore, Japan and U.S. have highest numbers of abnormally and negatively affected sectors. © 2021 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: dept.fin; peer-reviewed

Economic forecasts, anchoring bias, and stock returns - Birz, Gene; Dutta, Sandip; Yu, Han (Financial Management, 2021)
By utilizing survey forecasts of macroeconomic statistics, we find that market participants’ expectations are not rational as they exhibit an anchoring bias. The forecasts systematically underpredict macroeconomic statistics and the forecast errors are predicted by past macroeconomic announcements. Most importantly, we find that the stock market does not see through this bias, that is, we find statistically significant stock price effects of “anticipated” components of macroeconomic announcements. Investors overweight the importance of historical information and do not make sufficient adjustments after the arrival of new information. © 2021 Financial Management Association International
Keywords: dept.fin; peer-reviewed

Derivative use, ownership structure and lending activities of US banks - Abugri, Benjamin A; Osah, Theophilus Teye (Journal of Economics and Finance, 2021)
Following the 2007–2008 financial crisis, there is widespread interest in understanding how derivative use drives bank lending behavior. Our paper examines the impact of bank ownership structure on the relationship between derivative use and lending activities of U.S. banks. We find that lending recovered faster in larger banks than smaller banks post-crisis and in line with Diamond’s (Diamond DW 1984 Financial intermediation and delegated monitoring. Rev Econ Stud 51:393–414) systemic risk reduction theory, derivative use is positively associated with lending growth. Ownership is significant in explaining the magnitude of the relationship even after controlling for alternative specifications of the derivative use variable. In both normal and crisis periods, the speed of adjustment of lending to derivatives use by stock banks lags that of mutual banks. We suggest that speculative trading in derivatives substitutes for lending growth to a larger extent for stock banks compared to mutual banks. These findings may have important implications for investors and bank regulators. © 2020, Academy of Economics and Finance.
Keywords: dept.eco; dept.fin; peer-reviewed

Short selling prior to going concern disclosures - Huang, Jian; Wang, Lei; Yu, Han; Zhang, Zhen (Accounting and Business Research, 2020)
We provide insights into how the market processes going concern audit opinions based on the trading of some well-documented sophisticated investors–short sellers. We find that abnormal short selling increases significantly upon impending going concern disclosures. While prior literature attributed much of short selling around some corporate events to private information, we find evidence that pre-going-concern announcement short selling reflects both privately informed trading and processing of public information by short sellers. Further, a negative relation between pre-announcement short selling and post-announcement short-term stock returns exists for stocks with less short sale constraints. We also find moderate evidence associating short selling with subsequent bankruptcy to some extent. Overall, these results suggest that short sellers front run going concern announcements based on private information and fundamentals, although trading constraints prevent them fully impounding the severity of negative information in the short run, providing a partial explanation for the long-run price drift post-going concern. © 2020 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: dept.fin; peer-reviewed

The effect of political risk on shareholder value and the mitigating role of corporate social responsibility (CSR) - Chatjuthamard, Pattanaporn; Jiraporn, Pornsit; Sarajoti, Pattarake; Singh, Manohar (Managerial Finance, 2020)
Purpose: The study investigates the effect of political risk on shareholder value, using an event study and a novel measure of firm-level political risk recently developed by Hassan et al. (2017). In addition, the authors explore how corporate social responsibility (CSR) influences the effect of political risk on shareholder wealth. Design/methodology/approach: The authors exploit the guilty plea of Jack Abramoff, a well-known lobbyist, on January 3, 2006, as an exogenous shock that made lobbying less effective and less useful in the future, depriving firms of an important tool to reduce political exposure. Findings: The results show that the market reactions are significantly more negative for firms with more political exposure. Additional analysis corroborates the results, including propensity score matching, instrumental-variable analysis and Oster's (2019) method for testing coefficient stability. Finally, the authors note that the adverse effect of political risk on shareholder value is substantially mitigated for firms with strong social responsibility, consistent with the risk mitigation hypothesis. Originality/value: This study is the first to explore the effect of political risk on shareholder value using a novel measure. Furthermore, it is also the first to show that CSR alleviates the cost of political risk to shareholders. © 2020, Emerald Publishing Limited.
Keywords: CSR; Corporate social responsibility; Event study; Firm risk; G34; M14; Political risk; Shareholder wealth; dept.fin; dept.grad; peer-reviewed

The effect of relationship banking on firm efficiency and default risk - Yildirim, Alev (Journal of Corporate Finance, 2020)
Does relationship bank oversight reduce firm default risk and improve firm operational efficiency? I find that a new loan from a relationship bank reduces the default probability and increases the efficiency of a borrowing firm, benefiting both banks and borrowers. Moreover, inefficient and less creditworthy firms experience the highest reductions in their default risks and improvements in their efficiencies in the years following new relationship bank loans. Further, these benefits are disrupted when the relationship bank is acquired.
Keywords: Data envelopment analysis; Default risk; Firm efficiency; Relationship banking; Stochastic frontier analysis; Total factor productivity; dept.fin; peer-reviewed

Cohabitation before marriage: Do prior alliances enhance post-merger performance? - He, Zhaozhao; Yu, Han; Du, Lijing (Review of Quantitative Finance and Accounting, 2020)
We investigate the impact of prior alliance relationships on subsequent mergers between partner firms. We argue that an acquirer’s prior alliance experience with the target reduces information asymmetry, which helps improve acquisition performance. Alternatively, agency problems arising from familiarity may lead to inefficient decision making. Examining mergers between 1986 and 2014, we find evidence that prior alliance collaboration is positively associated with the acquirer’s long-term profitability and growth. This positive effect is more pronounced when target-specific learning and experience are more crucial to merger success, such as targets in knowledge-intensive or organizational-capital-intensive industries as well as cross-industry mergers. However, we cannot formally rule out the possibility that our results are partly driven by the small size of our sample.
Keywords: D80; G34; Information asymmetry; L14; L24; Learning and resources sharing; Mergers and acquisitions; O30; O32; Post-merger performance; Strategic alliance; dept.fin; peer-reviewed

The intra-industry effects of proxy contests - Chen, Fang; Huang, Jian; Yu, Han (Journal of Economics and Finance, 2020)
In this study, we examine the intra-industry effect of proxy contests. Proxy contests convey the information of common industrial risks or expected competitive relationship change. We find significant negative abnormal returns in the group of competitors of target firms with negative abnormal returns, and such negative abnormal returns become larger for similar-size competitors. In contrast, there are no significant abnormal returns for competitors of target firms with positive abnormal returns. These findings are consistent with the information-based theory but not the competitive theory. © 2019, Academy of Economics and Finance.
Keywords: Competitive effect; Information-based effect; Intra-industry effect; Proxy contest; dept.eco; dept.fin; peer-reviewed

CEO characteristics, firm performance, and corporate political contributions - Subrahmanyam, Vijaya; Singh, Manohar; Pennathur, Anita K. (Review of Financial Economics, 2020)
We investigate if CEO characteristics determine the choice of Political Action Committee (PAC) contributions by firms and if such participation leads to better firm performance. Using a unique, hand-collected database, we also focus on the identity of the politicians receiving PAC contributions to examine the impact of the value-relevance of such contributions. Examining data on corporate contributions made to candidates seeking federal office during the 2002, 2004, and 2006 election cycles, we find that CEO dominance and interest alignment influence strategic choices of firms with regards to establishing PACs. Our analysis of value-relevant contributions shows that firms prefer to donate to politicians representing the state of a firm's headquarters, validating the truth to the adage that all politics is local. However, these targeted political contributions do not have a discernible impact on firm performance.
Keywords: CEO characteristics; CEO dominance; agency theory; corporate political contributions; dept.fin; dept.grad; firm performance; peer-reviewed